Boko Haram: Religion and Violence in the 21st Century - Voll, John Obert (Religions, 2015)
Boko Haram in Nigeria provides an important example of the combination of religion and violence in the conditions of the twenty-first century. It is both a movement in the pattern of religiously-justified violence and a significant representative of the emergence of new types of modern terrorism in recent years. This article examines both of these aspects of Boko Haram as an example of religious violence. In the general development of religiously justified violence, Boko Haram is the heir to a long jihad tradition in West Africa. Its emergence follows well-established patterns of older militant Muslim groups, but it also departs significantly from those patterns as it shapes itself as a movement in the patterns of contemporary, twenty-first century modes of religious violence. Boko Haram is also identified, in twenty-first century terms, as a religious terrorist organization. As a religious terrorist group, it fits the pattern of what David Rapoport calls the fourth wavethe religious waveof modern terrorism. However, in the second decade of the twenty-first century, Boko Haram exhibits characteristics of a new style of religious terrorism that is more like the so-called Islamic State than the older type of terrorist organization of al-Qa'idah.